DNA methylation near the INS gene is associated with INS genetic variation (rs689) and type 1 diabetes in the Diabetes Autoimmunity Study in the Young. Issue 4 (28th February 2020) - Carry, Patrick M.; Vanderlinden, Lauren A.; Johnson, Randi K.; Dong, Fran; Steck, Andrea K.; Frohnert, Brigitte I.; Rewers, Marian; Yang, Ivana V.; Kechris, Katerina; Norris, Jill M.
Abstract: Objective: Mechanisms underlying the role of non‐human leukocyte antigen (HLA) genetic risk variants in type 1 diabetes (T1D) are poorly understood. We aimed to test the association between methylation and non‐HLA genetic risk. Methods: We conducted a methylation quantitative trait loci (mQTL) analysis in a nested case‐control study from the Dietary Autoimmunity Study in the Young. Controls (n = 83) were frequency‐matched to T1D cases (n = 83) based on age, race/ethnicity, and sample availability. We evaluated 13 non‐HLA genetic markers known be associated with T1D. Genome‐wide methylation profiling was performed on peripheral blood samples collected prior to T1D using the Illumina 450 K (discovery set) and infinium methylation EPIC beadchip (EPIC validation) platforms. Linear regression models, adjusting for age and sex, were used to test to each single nucleotide polymorphism (SNP) ‐probe combination. Logistic regression models were used to test the association between T1D and methylation levels among probes with a significant mQTL. A meta‐analysis was used to combine odds ratios from the two platforms. Results: We identified 10 SNP‐methylation probe pairs (false discovery rate (FDR) adjusted P  < .05 and validation P  < .05). Probes were associated with the GSDMB, C1QTNF6, IL27, and INS genes. The cg03366382 (OR: 1.9, meta‐ P = .0495), cg21574853 (OR: 2.5, meta‐ P = .0232), and cg25336198 (odds ratio: 6.6, meta‐ P = .0081) probes were significantly associated with T1D. The three probes were located upstream from the INS transcription start site. Conclusions: We confirmed an association between DNA methylation and rs689 that has been identified in related studies. Measurements in our study preceded the onset of T1D suggesting methylation may have a role in the relationship between INS variation and T1D development.